Said Nursi: A Brief Overview of Vision and Reformative Thoughts - Sethi, Muhammad Bilal; Jalal, Gulzar Ahmad; Haq, Sami ul (Journal of Islamic and Religious Studies, 2022)
The focus of the article is Said Nursi’s contributions in the fields of education, religion, and politics. Nursi was a Kurdish theologian, an Islamic scholar, and the most popular and influential intellectual of Turkish history. His influence and popularity among people are indicative of the titles he received from the people including “Badiuz-Zaman” (Wonder of the Age) and “Ustaad” (Muallam or teacher). Besides this, Nursi was widely famous among his people for his extravagant memory: his long-term memory was able to reproduce certain books. This reflects upon his unordinary personality as he was able to recite many books from memory. An unusual narrative about him was that when he used to read a page of a book, he would learn it by heart at the same moment. His vast study, intelligence, powerful memory, and oratory skills impressed his contemporaries to a great extent.